Primary cultivation: factors affecting contamination and Mycobacterium ulcerans growth after long turnover time of clinical specimens - Bratschi, M.W.; Bolz, M.; Grize, L.; Kerber, S.; Minyem, J.C.; Um Boock, A.; Yeboah-Manu, D.; Ruf, M.; Pluschke, G. (My University, 2014)
Abstract Background While cultivation of pathogens represents a foundational diagnostic approach in the study of infectious diseases, its value for the confirmation of clinical diagnosis of Buruli ulcer is limited by the fact that colonies of Mycobacterium ulcerans appear only after about eight weeks of incubation at 30°C. However, for molecular epidemiological and drug sensitivity studies, primary isolation of M. ulcerans remains an essential tool. Since for most of the remote Buruli ulcer endemic regions of Africa cultivation laboratories are not easily accessible, samples from lesions often have to be stored for extended periods of time prior to processing. The objective of the current study therefore was to determine which transport medium, decontamination method or other factors decrease the contamination rate and increase the chance of primary isolation of M. ulcerans bacilli after long turnover time. Methods Swab and fine needle aspirate (FNA) samples for the primary cultivation were collected from clinically confirmed Buruli ulcer patients in the Mapé Basin of Cameroon. The samples were either stored in the semi-solid transport media 7H9 or Amies or dry for extended period of time prior to processing. In the laboratory, four decontamination methods and two inoculation media were evaluated and statistical methods applied to identify factors that decrease culture contamination and factors that increase the probability of M. ulcerans recovery. Results The analysis showed: i) that the use of moist transport media significantly increased the recovery rate of M. ulcerans compared to samples kept dry; ii) that the choice of the decontamination method had no significant effect on the chance of M. ulcerans isolation; and iii) that Löwenstein-Jensen supplemented with antibiotics as inoculation medium yielded the best results. We further found that, ten extra days between sampling and inoculation lead to a relative decrease in the isolation rate of M. ulcerans by nearly 20%. Finally, collection and processing of multiple samples per patient was found to significantly increase the M. ulcerans isolation rate. Conclusions Based on our analysis we suggest a procedure suitable for the primary isolation of M. ulcerans strains from patients following long delay between sample collection and processing to establish a M. ulcerans strain collection for research purposes.